Can PPP Contracts Improve the Performance of the National Road Sector? - Josep Bely Utarja (PT Penjaminan Infrastruktur Indonesia (Persero), 2019)
This article attempts to answer two questions. The first is whether Public-Private Partnership (PPP) contracts can be easily implemented for national road preservation projects. The second is how the PPP contracts can increase the value for money (VfM) of the national road preservation budget. The institutional environment of national road sector is discussed first in order to highlight the particular role of road preservation contracts between the Government and the business sectors in that environment. Then, the discussion continued with types of contracts that have been used in this sector, historically. At the time of this writing, PPP contract has not been used in this sector. To approach this matter the next discussion is about PPP and VfM definition in the current regulation as well as their features in literature. Based on this discussion, characteristics comparison of the available types of contract is developed, including how these types of contracts, especially KPBU contracts, can be used to achieve VfM. The following section presents a simple simulation method to assess VfM achievement based on comparison of present value cost of public service comparator and PPP. The simulation is used to understand how the variables that determine VfM interact with each other in determining the final result. Finally, the last section contains the conclusions on how PPP contracts can increase the VfM of national road preservation project. Value for Money can be achieved using PPP contract if risks transferred from the Government to business / private entity is significant enough so that the combination of both incentives and the entity’s capability can reduce the total cost of risks more than to compensate the difference between the entity’s cost of capital and the Government cost of capital. In this case, the scale of the project is also important, given the complexity of PPP contract resulted in relatively higher transaction costs compare to other types of contracts. This article does not discuss the design of performance-based incentive-oriented contract for national road preservation projects. In addition, the risks analysis done in the numerical simulation is simplified and, thus, requires further data collection for more detailed application. The externalities come from the construction phase to the operational and maintenance phase have not yet based on empirical evidence in this sector. This article also does not address issues on how to create level of competition in the procurement stage as well as in the operational stage that can promote value for money. Lastly, the risks discussed in the types of contracts only limited to supply risks. The use of PPP contracts to replace conventional procurement contracts will not automatically reduce primary balance deficit. Assessments and steps to ensure the achievement of value for money from the PPP contract must be done and planned in advance. This is the first article discussing value for money from PPP contract for Indonesian national road preservation projects.